Improvement in lithium-ion transport performance of cathodes by PEGDA-based solid-state electrolyte - Zhang, Yongquan; Zhu, Baoshan; Chi, Qingguo; Gao, Hongchang; Zhang, Changhai; Zhang, Tiandong; Zhu, Kai; Cao, Dianxue (Frontiers in Energy Research, 2022)
The transport performance of lithium ions affects the rate performance of the cathode at different current densities. The poor interface contact between a solid electrolyte and the cathode makes it difficult to transport lithium ions. Adding a solid electrolyte into the cathode material can improve lithium ion transport. In this paper, we prepared some cathodes with different doping ratios, including two common cathode materials (LiFePO4 and NCM811), and tested their rate and long cycle performance. LFP-10 has a specific discharge capacity of 79.75 mAh g−1 at 5C, and the Li+ diffusion coefficient of LFP-10 is 4.91 × 10−13 cm−2 s−1, which is about 13.4 times higher than the pure LiFePO4 sample. The rate performance of an all-solid-state battery has also been improved, and there is still more than 100 mAh g−1 capacity reserved at 60°C and 2C current density. This shows that the introduction of a PEGDA-based solid electrolyte can significantly improve the Li+ transport of the cathode, and the composite cathode also provides support for the future application of all-solid-state batteries.